Aplikasi Enkripsi dan Dekripsi Short Message Service di Android Menggunakan Metode Blowfish - Fahriah, Wildatunnisa; Febrianto, Tulus (Universitas Trilogi, 2019)
Short Message Service (SMS) is a communication technology that is very popular. By using SMS someone can exchange messages with others. However, with the wiretapping issue sms, a person no longer has the right to privacy. So the program was made on a mobile phone-based application that will change the android SMS messages into codes so that information from SMS in not known by others. When sending SMS, this application will encrypt the message into shape with a key codes entered by the sender. And when the acceptance of SMS, this application will describe the codes message into form of the original message using the same key with the sender. This application was made in the android based application to send an important message to others without fear of being noticed by others. The method used in the application to encrypt and decrypt the messages are methods Block Cipher Algorithm or also called blowfish method and its implementation using the java programming language with the android mobile platform